THE CIVILIZING MISSION UNVEILED: A POSTCOLONIAL CRITIQUE OF RUDYARD KIPLING’S KIM - Srivastava, Himanshu A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores Rudyard Kipling’s Kim through a postcolonial lens, critically engaging with the novel’s portrayal of the British Empire’s civilizing mission in India. Set in late nineteenth-century colonial India, the narrative follows the adventures of Kimball O’Hara, an orphaned Irish boy, who navigates both British and Indian identities. The study examines how Kim reflects, reinforces, and subtly critiques the ideology of the civilizing mission through its complex portrayal of characters, race, culture, and power dynamics. While the novel largely upholds imperial ideals, such as the benevolent authority of British officials and the loyalty of native collaborators, it also reveals inherent contradictions. By analyzing the representations of native characters like the Lama, Hurree Chunder Mookerjee, and Mahbub Ali, the paper highlights the tension between admiration for native cultures and the underlying paternalism of the imperial project. Additionally, the hybrid identity of Kim, whose loyalty to both British and Indian causes challenges colonial binaries, complicates the straightforward narrative of imperial benevolence. Ultimately, the study asserts that Kim functions as a nuanced text that not only reinforces colonial ideologies but also critiques their moral and cultural limitations, offering valuable insights into the complexities of colonial representation and the legacies of empire. Kipling introduces him early in the novel as “a poor white of the very poorest,” yet one who “spoke the vernacular by preference, and knew native life as he knew the passages of his own house” (Kipling 5).